Management model with processes to identify seismic vulnerability in housing - Del Carpio Delgado, Fabrizio; Vera Barrios, Bertha Silvana (Revista Ingeniería de Construcción, 2021)
Seismic events for decades have caused great prejudice to countries causing human and economic losses due to the collapse of houses, therefore the relevance of this research lies in offering a management model with processes to identify the seismic vulnerabilities of houses and validate the correlation between whether there is dependence between the Knowledge of the Management Model with Processes and its application (hypothesis). A mixed method (quantitative and qualitative) is presented, generating reliable and concise results, issuing Chi-Square values to prove that they are greater than 0.05, implying a very weak or low dependence relationship. Consequently, it is concluded with a confidence level of 95%, indicating the way in which the knowledge of the model is developed and its application, has very little dependence in the local governments of the Moquegua Region, since they do not know the proposed model.